Prevalence, New Incidence, Course, and Risk Factors of PTSD, Depression, Anxiety, and Panic Disorder during the Covid-19 Pandemic in 11 Countries - Georgieva, Irina; Lepping, Peter; Bozev, Vasil; Lickiewicz, Jakub; Pekara, Jaroslav; Wikman, Sofia; Loseviča, Marina; Raveesh, Bevinahalli Nanjegowda; Mihai, Adriana; Lantta, Tella (Healthcare (Basel, Switzerland), 2021)
We aimed to evaluate the prevalence and incidence of post-traumatic stress disorder (PTSD), depression, anxiety, and panic disorder (PD) among citizens in 11 countries during the Covid-19 pandemic. We explored risks and protective factors most associated with the development of these mental health disorders and their course at 68 days follow up. We acquired 9543 unique responses via an online survey that was disseminated in UK, Belgium, Netherlands, Bulgaria, Czech Republic, Finland, India, Latvia, Poland, Romania, and Sweden. The prevalence and new incidence during the pandemic for at least one disorder was 48.6% and 17.6%, with the new incidence of PTSD, anxiety, depression, and panic disorder being 11.4%, 8.4%, 9.3%, and 3%, respectively. Higher resilience was associated with lower mental health burden for all disorders. Ten to thirteen associated factors explained 79% of the variance in PTSD, 80% in anxiety, 78% in depression, and 89% in PD. To reduce the mental health burden, governments should refrain from implementing many highly restrictive and lasting containment measures. Public health campaigns should focus their effort on alleviating stress and fear, promoting resilience, building public trust in government and medical care, and persuading the population of the measures' effectiveness. Psychosocial services and resources should be allocated to facilitate individual and community-level recovery from the pandemic.
Keywords: Covid-19; anxiety; panic disorder; general population; risk factors; depression; resilience; pandemic; PTSD; multinational study; mental health